The Influence of Viral Marketing and Online Customer Reviews on Purchase Decisions - Ahmad Muhammad Rizal Fatkurrohman; Farhan Sabbihis Hanan; Yusuf Yusuf (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of digital technology has transformed consumer behavior in making purchasing decisions. Social media and e-commerce platforms have become the primary sources for obtaining product-related information, making viral marketing and online customer reviews crucial factors in the decision-making process. This study aims to analyze the influence of viral marketing and online customer reviews on consumer purchase decisions, both partially and simultaneously. A quantitative approach was employed using purposive sampling, with a total sample of 130 university students in Cirebon City who use the TikTok e-commerce platform. Data were collected through a Google Form questionnaire using a four-point Likert scale. Validity and reliability tests were conducted to ensure the accuracy of the research instruments, while data analysis involved normality tests, coefficient of determination, F-tests, and multiple linear regression analysis using SPSS. The findings indicate that viral marketing and online customer reviews significantly influence purchase decisions. Viral marketing enhances brand awareness and emotional appeal, whereas online customer reviews serve as a trustworthy source of information that strengthens consumer trust and purchase intention. These two factors complement each other in shaping consumer perceptions of a product or service.